Budaya Pendidikan dan Budaya Organisasi Serta Jaringan Komunikasi Dalam Pendidikan - Rifai, Muhammad; Syahputra, Muhammad Rizki; Thaiyibah, Afifah; Mardiana, Mardiana; Pohan, Hadi Lapian (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study examines the interaction between educational culture, organizational culture, and communication networks in the context of Al-Hadi School. Using a qualitative case study approach, this research digs deeper into the fundamental values, norms and practices that shape the school learning environment. The findings reveal that Al-Hadi culture emphasizes discipline, adherence to religious values, and innovative teaching methods. While these elements have fostered a strong sense of community, they have also influenced the development of formal and hierarchical communication networks.